Crop kites: Determining crop-water production functions using crop coefficients and sensitivity indices. (November 2016) - Smilovic, Mikhail; Gleeson, Tom; Adamowski, Jan
Highlights: Crop kites demonstrate yield as a function of the temporal distribution of water use. The timing of water deficit significantly affects water productivity and yield. Deficit irrigation necessitates acknowledging the timing of water deficit. Crop kites are a tool to easily determine crop-water production functions. Crop-water production functions are not necessarily diminishing curvilinear functions. Abstract: The crop-water production function quantitatively evaluates the relationship between seasonal water use and crop yield and is used to evaluate optimal irrigation depth and assess the potential of deficit and supplemental irrigation. A simple and easily applicable methodology to develop crop- and region-specific crop-water production functions using crop coefficients and sensitivity-indices is presented. Previous efforts to describe the crop-water production function have not accounted for the effects of the temporal distribution of water use and trivialize the associated variability in yields by assuming an optimized or arbitrary temporal distribution. The temporal distribution of water use throughout the growing season can significantly influence crop yield, and the ability of farmers to manage both the timing and amount of irrigation water may result in higher yields. We propose crop kites, a tool that explicitly acknowledges crop yield as a function of the temporal distribution of water use to both evaluate the complete space of water use and crop yield relationships, and extract from this space specific crop-water production functions. An example for winter wheat is presented using previously validated crop-specific sensitivity indices. Crop-water production functions are extracted from the crop kite related to specific irrigation schedules and temporal distributions of water use. Crop-water production functions associated with maximizing agricultural production agree with previous efforts characterizing the shape as a diminishing curvilinear function. Crop kites provide the tools for water managers and policy makers to evaluate crop- and region-specific agricultural production as it relates to water management and the associated economics, and to determine appropriate policies for developing and supporting the infrastructure to increase water productivity. Graphical abstract: